Monetary versus grade incentives depending on personality traits: A field experiment on undergraduate students’ performance - Noemí Herranz-Zarzoso; Gerardo Sabater-Grande (Heliyon, 2023)
This study aims to examine the role of personality on the effectiveness in improving students' performance of two extrinsic incentives: monetary and grade incentives. To achieve this goal, we conducted a randomized field experiment in which students in a Microeconomics course were offered the opportunity to participate in a practice test program, with no effects on the grade of the course itself. In the call to participate, students were informed that participants would be randomly assigned to one of two groups. Whereas in the control group students would not be monetarily incentivized, participants assigned to the treatment group would be paid according to their performance in the practice tests. In addition, we elicited the big five personality and risk aversion traits of the participants (168 undergraduates). All subjects received grade incentives in the later official course exam, in which no monetary incentives were offered. We used non-parametric tests to carry out both between-subjects and within-subjects performance comparisons. Controlling for potential confounding factors like students' gender and academic record, our OLS regressions indicate that although monetary incentives are effective in improving students’ performance in practice tests, their effect does not carry over to the course exam. Furthermore, we find that the effectiveness of grade incentives (used in the course exam) on improvement as a substitute for monetary incentives (adopted in practice tests), is higher the more conscientious the students are.